Design, Synthesis and Biological Evaluation of Novel Indole-2-Carboxamide Derivatives as Anti-Tubercular Agents - Alsayed, Shahinda Sayed Rabie (Curtin University, 2021)
The thesis entails the design, synthesis and biological evaluation of novel small molecules as potential antitubercular and/or antitumour agents.